Analisis Yuridis Terhadap Perubahan Status Perjanjian Kerja Waktu Tertentu Menjadi Waktu Tidak Tertentu Berdasarkan Peraturan - Syahdan Syahdan; Yana Sukma Permana (HUMANIORUM, 2026)
This study aims to analyze the application of the principle of substantive justice in the conversion of Fixed-Term Employment Agreements (PKWT) into Indefinite-Term Employment Agreements (PKWTT) under Indonesian labor law. The issue arises from the misuse of PKWT for permanent and continuous work, which disadvantages workers and creates inequality in industrial relations. This research employs a normative legal method using statutory and conceptual approaches through literature review of legislation, legal doctrines, and relevant court decisions. The findings indicate that the legal framework governing the conversion of PKWT into PKWTT is clearly stipulated in Law No. 13 of 2003 as amended by Law No. 6 of 2023 and Government Regulation No. 35 of 2021. Such conversion functions as an automatic legal protection mechanism when the legal requirements of PKWT are violated. The application of substantive justice in this conversion seeks to ensure job security, protection of workers’ normative rights, and balance between workers’ and employers’ interests. However, its effectiveness is hindered by weak supervision, formalistic legal approaches, and limited legal literacy among workers. Therefore, synergy among the government, employers, and workers is essential through regulatory strengthening, effective supervision, social dialogue, and empowerment of labor unions to achieve fair, harmonious, and sustainable industrial relations